Research on Tracking Resistance of Silicone Rubber Based on Laser-induced Breakdown Spectroscopy. (November 2020) - Hua, Ren; Heng, Xu; Shanqiang, Gu; Kun, Chen; Chao, An; Nan, Liu
Abstract: Silicone rubber composite materials are widely used in the external insulation equipment of power systems, and the tracking resistance grade is one of the indicators used for evaluating the performance of silicone rubber. It is of great significance to quickly detect the tracking resistance of insulator materials on site. The existing tracking resistance tests are all laboratory tests performed after sample preparation, and there is a lack of on-site detection methods. The laser-induced breakdown spectroscopy (LIBS) method was used to establish the linear relationship between the amount of ablation due to tracking and the background radiation intensity of the experimental LIBS spectrum, and the influence of silica and alumina trihydrate (ATH) fillers on the material's tracking resistance was studied. This study showed that the LIBS technology can be used to detect the tracking resistance of silicone rubber materials.